Padrões visuais para capas de sketchbooks inspirados em elementos culturais do estado do Amazonas - Brazão, Kaina Bruno (Brasil, 2022)
The state of Amazonas, also known for its biodiversity, has a very expressive socio-diversity and cultural wealth. However, there are few products and services related to this theme. Either, it is possible to observe the non-valuation of these elements by the local population. Thus, by combining Surface Design (an area that allows the generation of ideas and differentiated, innovative, and attractive products) and sketchbooks, which are affordable and widely available products on the market, this project aimed to create patterns inspired by cultural elements of Amazonas for application in sketchbook covers. Therefore, it was possible to value, propagate and spread the region's culture. To achieve this goal, the Design methodologies of Munari (2008) and Oliveira (2012) were used. The adopted procedures consisted of the study of the culture of the Amazonas, the concepts and techniques of Surface Design, and the materials needed to carry out the project. In addition, were performed similar analysis, questionnaires, and briefing, besides elaborating design requirements and parameters and a semantic panel from the data collected. As a result, three patterns depicting elements of the consuetude and habits of the Amazonian population for sketchbook covers were created. In this way, it was possible to reinforce the importance of using the Design as an aid in the creation of innovative and attractive products and the appreciation of the state's cultural elements.